2014
DOI: 10.2147/opth.s59700
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative endoscopic observation of sclerotomy site after cannula removal for 23-gauge vitrectomy

Abstract: BackgroundThe purpose of this study was to determine the incidence of vitreous incarceration in sclerotomy after cannula removal during 23-gauge vitrectomy.MethodsThirty-seven eyes underwent 23-gauge sutureless vitrectomy. Oblique sclerotomies were made parallel to the limbus and tangentially to the sclera. Once past the trocar sleeve, the angle was changed to 90 degrees perpendicular to the surface and the trocar and cannula inserted. Vitreous gel was removed until the intraocular edge of the infusion cannula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“… 10 A study in patients evaluating the sclerotomy site endoscopically through another cannula in 32 eyes that underwent 23-gauge non-valved cannula vitrectomy found no vitreous incarceration in 30 eyes (94%) when one cannula was removed with insertion of a light probe, with only minimal vitreous incarceration observed in the other two eyes. 11 Experimental models in porcine cadaver eyes showed that interposing a light probe through the cannula during its removal reduced the rate and severity of vitreous incarceration. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“… 10 A study in patients evaluating the sclerotomy site endoscopically through another cannula in 32 eyes that underwent 23-gauge non-valved cannula vitrectomy found no vitreous incarceration in 30 eyes (94%) when one cannula was removed with insertion of a light probe, with only minimal vitreous incarceration observed in the other two eyes. 11 Experimental models in porcine cadaver eyes showed that interposing a light probe through the cannula during its removal reduced the rate and severity of vitreous incarceration. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%